CAMPUR KODE DIALEK MELAYU SEKADAU PADA MAHASISWA UNIVERSITAS PGRI PONTIANAK - Fitri Wulansari; Siti Khairiah; Devita Aprillia; Anggita Putri; Yohana Lilis (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study is designed to elucidate the patterns, categories, and social purposes of borrowing elements of the Sekadau dialect of Malay in the speech of students at PGRI University of Pontianak from a sociolinguistic perspective. The focus of this study is limited to the use of Indonesian, the Sekadau Malay dialect, and English in conversations among students in an academic setting. The approach adopted is qualitative descriptive, with data collection methods including non-intrusive participatory observation (SBLC), audio recording, and detailed note-taking. The study material consists of students’ spoken utterances containing code-mixing phenomena, which were then processed through information reduction, presentation of findings, and synthesis of conclusions. The findings indicate the existence of three classifications of code-mixing: internal, external, and combined, with a prevalence of internal code-mixing characterized by the insertion of the Sekadau Malay dialect into Indonesian. Significant research results indicate that the use of regional dialects functions not only as a means of communication but also as a symbol of identity and social cohesion, and is influenced by the forces of globalization through the adoption of English. Therefore, the code-mixing phenomenon reflects shifts within society and multilingual identity among students.